Стан Підземної Обсерваторії Нейтрино в Жіангмені - Schever, M. (Publishing house "Academperiodika", 2019)
The Jiangmen Underground Neutrino Observatory (JUNO) is a next generation multipurpose antineutrino detector currently under construction in Jiangmen, China. The central detector, containing 20 kton of a liquid scintillator, will be equipped with ∼18 000 20 inch and 25 600 3 inch photomultiplier tubes. Measuring the reactor antineutrinos of two powerplants at a baseline of 53 km with an unprecedented energy resolution of 3%/√︀E(MeV), the main physics goal is to determine the neutrino mass hierarchy within six years of run time with a significance of 3–4q. Additional physics goals are the measurement of solar neutrinos, geoneutrinos, supernova burst neutrinos, the diffuse supernova neutrino background, and the oscillation parameters sin2 O12, Δm212, and |Δm2ee| with a precision <1%, as well as the search for proton decays. The construction is expected to be completed in 2021.